Code of Professional Ethics for Police Members Who Commit Criminal Acts - Azhari, Azhari; Asmi Hasibuan, Saiful (PT. Multidisciplinary Press Indonesia, 2024)
The code of ethics is a moral and ethical standard that must be followed by members of the Indonesian National Police in carrying out their duties. This article discusses the role and impact of the code of ethics on members of the Indonesian National Police who commit crimes. In a legal environment, the code of ethics serves as a guideline for behavior that ensures that members of the Indonesian National Police act in accordance with the values of justice, professionalism, and integrity. When members of the Indonesian National Police violate this code of ethics, they face not only legal consequences, but also internal sanctions that can include reprimands, demotions, and even dismissal. This article also explores how enforcing the code of ethics can strengthen public trust in the police institution and prevent abuse of authority. This study uses a qualitative method with a case study approach to analyze various examples of violations of the code of ethics committed by members of the Indonesian National Police and how the police institution handles these violations. The results of the study indicate that the application of a firm and consistent code of ethics is a key factor in maintaining discipline and professionalism within the Indonesian National Police, as well as in improving the institution's image in the eyes of the public. In conclusion, the code of ethics not only functions as a supervisory tool, but also as a vital moral foundation for maintaining integrity and trust in law enforcement in Indonesia.